Jennifer Forestal (2021). Designing for Democracy How to Build Community in Digital Environments. Oxford, University Press. - Sousa, João Carlos (Estudios sobre el Mensaje Periodístico, 2024)
Jennifer Forestal is a Professor of Political Science at Loyola University Chicago and her academic and working career is at the confluence of architecture and politics. Recently, she has been studying the role of space and how it is organised politically, especially in relation to digital platforms such as Facebook or Twitter. A cross-cutting feature of his work is the strong influence of John Dewey and the way in which the participatory model idealised by the American author can be adapted to digital space. The work we now present, Designing for Democracy How to Build Community in Digital Environments, is the main work of this researcher who represents a novelty in the field of digital policy studies. This work is organised organically into six chapters, all with a strong reflexive and qualitative bent.